(untitled) (Research, Society and Development, 2020)
This article aims to describe the contingency plan of a specialized clinic for patients with chronic heart failure to act during the COVID-19 pandemic. This is an experience report on the actions developed through remote care of heart failure patients and their caregivers, based on the Primary Nursing model, in a clinic located in Niterói/RJ/Brazil. The intervention has been implemented since March 2020 in a web system called “Sistema Coração Valente” and the data is being stored in a database that uses MySQL. Obtained as a result the report of the actions used during the isolation of social faith described chronologically, considering the planning, implementation and evaluation of results. Then, it is concluded the contingency plan of the “Clínica de Insuficiência Cardíaca Coração Valente” for telephone consultations, based on the Primary Nursing model, proved to be effective in the remote monitoring of patients with heart failure.